AI in Cybersecurity: Transformative Approaches to Safeguarding Information Technology Systems - Marzoog Al-Mukhtar, Wijdan Noaman (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
AI in cybersecurity has significantly changed how businesses secure their IT systems against increasingly sophisticated and ever-evolving cyberattacks. AI solutions that leverage machine learning, deep learning, and data analytics analyze patterns in threat behavior to identify and predict threats, enabling immediate responses that help organizations stay ahead of emerging threats. However, this revolutionary approach also introduces several challenges related to ethics and technology, including security vulnerabilities, data quality issues, bias in AI models, and questions of responsibility and privacy. As AI continues to progress, innovations such as behavioral biometrics, quantum computing, and autonomous security systems could become viable means of strengthening future cyber defenses. This paper discusses the current application of artificial intelligence in cybersecurity, reports on the challenges faced by AI systems, and outlines potential future developments that could revolutionize cybersecurity policies. It aims to raise awareness among practitioners and scholars about the importance of AI technologies in cybersecurity, providing a comprehensive analysis of AI-driven cybersecurity solutions.